The behavior of semi-rigid polyurethane film based on functionalized rubber by one-shot and two-shot method preparation - Hirzin, Radin Siti Fazlina Nazrah; Azzahari, Ahmad Danial; Yahya, Rosiyah; Hassan, Aziz; Tahir, Hairani (Springer Verlag, 2018)
Semi-rigid polyurethane (PU) films based on functionalized liquid natural rubber (FLNR) were prepared by one-shot and two-shot methods. FLNR derived from waste crumb rubber acted as the soft segment and the hard segment consisted of 4,4′-methylenebis-(phenylisocyanate) (MDI) and 1,4-butanediol (BDO). The urethane linkage formation was confirmed by FTIR with a –NH-peak at 3317 cm −1 and disappearance of the NCO peak at 2295 cm −1 . The semi-rigid PU with low rubber polyol chain favored solubility in non-polar solvent (toluene and chloroform) and low polar solvent (THF). For semi-rigid PU with high rubber polyol chain, it was poorly soluble in any solvent thus it has high stability. Studies on the hydrolytic stability were shown to be highly influenced by the high rubber polyol chain (soft segment contents more than 60%) in semi-rigid PU composition. The thermal stability of semi-rigid PU as determined by thermogravimetric analyses (TGA) showed improved degradation stabilities (more than 270 °C) in the presence of BDO and higher molecular weight of FLNR.